Kuuk, Skrap, and the Resistance Vernacular - Jon Mikkel Broch Ålvik (Nordlit: Tidsskrift i litteratur og kultur, 2020)
How are gendered identities enabled, contested, and performed through Nordic popular music? Building on relevant approaches in popular music analysis, this article offers an investigation into the function/s of language and musical style in enabling and engendering agency and subjectivity via two case studies in Norwegian popular music.